Continuous Spinal Anesthesia: Dose Requirements and Characteristics of the Block. Issue 1 (January 1993) - Petros, A. J.; Smith, D.; Barnard, M.; Ronzoni, G.; Carli, F.
Abstract : Background and Objectives: A fine-bore 28G CoSpan spinal catheter was used to provide continuous spinal anesthesia for major upper and lower abdominal, peripheral vascular, and orthopedic surgery in 90 patients, aged 31-91 years. Methods: Initial doses (0.5-2.0 mL) of hyperbaric bupivacaine 0.5% were given and followed, if needed, by additional doses of 0.5-1.0 mL to achieve a satisfactory blockade for the proposed type of surgery. The incidence of hypotension, ambulatory postdural puncture headache, and technical problems encountered with insertion of the spinal catheters were recorded. Results: The technique of continuous spinal anesthesia was successful and easy to learn. Satisfactory sensory and motor blockade was achieved within 12-18 minutes, and surprisingly small amounts were needed in those patients undergoing limb surgery. Conclusions: Mild postdural puncture headache occurred in four patients, but none of the patients required blood patch. One catheter broke during removal; since then, it has been our policy to remove a catheter with the patient in a flexed position.